Taxonomic significance of morphology and palynology of two species of Dracaena found in south eastern Nigeria - Ilodibia, Chinyere; Okeke, Clement; Chukwuma, Maureen; Okeke, Nneka; Akachukwu, Ebele; Aziagba, Bibian (International Journal of Biological Research, 2014)
Morphology and Palynology were carried out on Dracaena mannii Bak and Dracaena arborea Link various parts. T test was used for the analyses. Morphologically, the leaves of D. arborea are longer and wider than those of D. mannii, and the length of the internode of D. arborea is more than those of the D. mannii. Both species are trees and have the same inflorescence, floral, fruit and seed Morphology. Palynologically, the pollen grains of the two species are monocolpate with scabrate surfaces. The colpus in D. mannii is longer than that of D. arborea. The result also showed that there was no significant difference in the sizes of the pollen grains, the pollen form indices as well as length and diameter of the colpi of both D. arborea and D. mannii. The overall analyses showed no significant statistical difference in the morpology and palynology of the two Dracaena species. The implication is that the two species are closely related and this justified their placement under the same genus Draceana while the slight differences between them suggest the reason for their separation into different species.